Challenges and strategies for implementing the Ramsar Convention. Balancing Economic Development and Wetland Conservation - Dragomir, Andreea-Nicoleta; Florescu, Ioana (Studia Ecologiae et Bioethicae, 2024)
Ramsar Convention on Wetlands of International Importance, particularly focusing on waterfowl habitats, signifies a pivotal shift in global attitudes towards wetland conservation. Historically viewed as hindrances to development, wetlands have suffered from drainage and reclamation efforts, resulting in significant biodiversity loss. However, a growing recognition of their ecological significance has spurred international action. The Convention, established in 1971, serves as a landmark agreement to safeguard wetland ecosystems. It mandates member states to designate and conserve wetlands within their territories, emphasizing the importance of international cooperation due to the transboundary nature of wetland ecosystems. The Convention’s objectives encompass sustainable development goals, including water quality, biodiversity, and climate change mitigation. Implementation relies on national policies and collaboration among stakeholders. Furthermore, the Convention aligns with other environmental agreements, fostering synergies to enhance wetland protection globally. Despite these positive developments, there are significant challenges in ensuring the effective implementation of the Convention, particularly when economic interests conflict with environmental conservation. As highlighted in the case of the Bystroe Canal project in the Danube Delta, balancing development with wetland protection remains a critical issue. This article addresses the question of whether the Ramsar Convention can effectively apply its provisions in such cases, arguing that while it provides a strong framework, its effectiveness is often undermined by competing economic priorities. Without stronger enforcement mechanisms and increased international cooperation, the objectives of the Convention risk being compromised.